The Use of Aquacrop Model for Soybean in Various Water Availability Within a Lysimeter System - Ramadhani, Farchan Mushaf Al; Bowo, Cahyoadi; Slameto, Slameto (Green Engineering Society, 2023)
The AquaCrop model is widely used under various agro-ecological conditions to reduce farm water consumption. The study aimed to simulate, validate, and measure the performance of AquaCrop models for canopy cover, biomass and soybean crop yields cultivated within a lysimeter. This research was conducted in the experimental field of the Faculty of Agriculture, the University of Jember, Indonesia (8°09'45.1